Puerarin transport across rat nasal epithelial cells and the influence of compatibility with paeoniflorin and menthol - Zhang L; Du S; Lu Y; Liu C; Wu H; Tian Z; Wang M; Yang C (Dove Medical Press, 2017)
Lin Zhang, Shou-Ying Du, Yang Lu, Chang Liu, Hui-Chao Wu, Zhi-Hao Tian, Min Wang, Chang Yang School of Chinese Materia Medica, Beijing University of Chinese Medicine, Chaoyang District, Beijing, People’s Republic of China Abstract: Nose-to-brain transport can provide an excellent pathway for drugs of the central nervous system. Consequently, how to make full use of this pathway in practical applications has become a focus of drug design. However, many aspects affecting drug delivery from the nose to the brain remain unclear. This study aimed to more deeply investigate the transport of puerarin and to explore the mechanism underlying the influence of compatible drugs on puerarin permeability in a primary cell model simulating the nasal mucosa. In this research, based on rat nasal epithelial cells (RNECs) cultured in vitro and cytotoxicity assays, the bidirectional transport of puerarin across RNEC monolayers and the effect of its compatibility with peoniflorin and menthol were analyzed. The apparent permeability coefficient was <1.5×10–6 cm/s, and the efflux ratio of puerarin was <2, indicating that puerarin had poor absorption and that menthol but not peoniflorin significantly improved puerarin transport. Simultaneously, through experiments, such as immunofluorescence staining, transepithelial electrical resistance measurement, rhodamine 123 efflux evaluation, the cell membrane fluorescence recovery after photobleaching test, and ATPase activity determination, the permeability promoting mechanism of menthol was confirmed to be closely related to disruption of the tight junction protein structure, to the P-glycoprotein inhibitory effect, to increased membrane fluidity, and to the promotion of enzyme activity. These results provide reliable data on nasal administration of the studied drugs and lay the foundation for a deeper investigation of the nose–brain pathway and nasal administration. Keywords: Chinese herbal compound, immunofluorescence, transepithelial electrical resistance, tight junction, P-glycoprotein, membrane fluidity